(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
This study was aimed at screening microorganisms isolated from dump sites for polymer production. Five samples of dump site soil were gathered from each of 10 distinct sites, totaling fifty samples, throughout the collection process. Microorganisms were isolated using the pour plate method. Bacteria isolates were identified using biochemical tests and molecular analysis using 16S rRNA gene primer while morphological characteristics are 18SrRNA gene primer were used to identify fungi isolate. Screening of the organisms for polymer production was done using Sudan Black Band Nile Blue A. The polymer extracted were analyzed using Fourier Transform Infrared Spectroscopy(FTIR) and Scanning Electron Microscope (SEM). Results revealed the presence of five fungi and seven bacterial species identified to be Aspergillus niger, Penicillium chrysogenum, Penicillium marneffei, Cladosporium tenuissimum and Rhizopus sp., while bacterial isolates were identified as Bacillus licheniformis, Bacillus cereus, Paenibacillus polymyxa, Bacillus megaterium, Bacillus mycoides, Bacillus subtillis and Enterobacter species. Only four bacterial isolates were positive for polymer production and molecularly identified as Bacillus subtilis strain AGB1 (OM273871), Bacillus megaterium strain AGB2 (OM216844), Paenibacillus polymyxa strain AGB3 (OM273889) and Bacillus licheniformis strain AGB4 (OP703543).The polymer has rough surfaces and crystalline in nature, while FTIR result indicated that the polymer had C=O carbonyl functional group and identified as polyhydrxybutyrate (PHB) polymer while SEM showed that it has crystalline surface. It can be concluded that bacterial isolates which were polymer producers can be utilized for large-scale production of polyhydroxybutyrate for industrial purposes